On Wiener Process Degradation Model for Product Reliability Assessment: A Simulation Study. (7th November 2022) - Hove, Herbert; Mlambo, Farai
Abstract : This paper examines the application of the Wiener process as a degradation model. Its appropriateness as a degradation model is discussed and demonstrated with the aid of Monte Carlo simulations. In particular and for monotonically degrading systems, this paper demonstrates that the irreversible accumulation of damage can be modelled by the Wiener maximum process. First passage times of the Wiener and its maximum process are also revealed to coincide. Practical advantages of assessing system reliability from degradation data are highlighted by applying the Wiener process model to a real gallium arsenide (GaAs) laser data for telecommunication systems. The real data application results demonstrate that degradation analysis allows for conclusions about system reliability to be reached earlier without compromising estimation accuracy—a major practical advantage.